(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Recent incidents of Manipur killing many innocent people have shaken the whole idea of peaceful coexistence. The video viral from Manipur touches my hart. Being a peace educator I am writing this paper how to infuse peace components in school curriculum so that we will live in peace and harmony in the society. Peace is disturbed both at the macro and micro levels. There are many concerns that we need to consider in order to establish internal as well as external peace especially during the last few decades that the prevailing system of education in the world would not necessarily lead us towards a safe and peaceful future. It is important to note that the culture of violence and terrorism is generated and supported by the people preoccupied with their biases and hatred-based values; our education system is playing a complementary, if not causative, role in sustaining intolerance and extremism. In the cultural context it is said that today’s so-called modernity and urbanity is leading us towards a society deprived of peace-generating social values. The values handed down from one generation to another through the modern structured education systems are based on curriculums approved by the interests of nation states.